7E Learning Cycle Based Interactive Learning Media as Alternative Teaching Material in Vocational High Schools - Mahendra, I Gede Budi; Rapar, Jocke Jonathan; Killis, Billy; Memah, Viverdy (IJIE (Indonesian Journal of Informatics Education), 2024)
A high-quality learning process is crucial for enhancing the competitiveness of graduates in the professional world. Teaching materials such as Interactive Learning Media have an important role in enabling students to gain knowledge and be actively involved in learning activities. The objective of this study is to develop, evaluate the feasibility, and determine the impact of implementing 7E Learning Cycle Based Interactive Learning Media. This research followed the R&D approach using the ADDIE model. The research subjects included 2 material experts, 2 media experts, 2 language experts, 36 XI TITL students, and 2 subject teachers determined by purposive sampling. The research instrument uses interview guidelines, questionnaire sheets and test questions. Data collection was conducted through interviews, questionnaires and tests. The research findings indicate that 7E Learning Cycle Based Interactive Learning Media is very valid, with a validity level of 85% according to media experts, 79% according to subject matter experts, and 79% according to language experts. The practicality test yielded results of 82% for students and 87% for teachers, falling under the category of "very practical." The evaluation results demonstrated an average score increase of 6.29. It is recommended that students utilize the 7E Learning Cycle Based Interactive Learning Media to facilitate meaningful learning experiences, foster critical thinking skills, promote independence, and enhance conceptual understanding of the subject matter. Furthermore, subject teachers are encouraged to utilize the outcomes of this Interactive Learning Media Development as a framework for developing teaching materials on other topics.